DESENVOLVIMENTO E VALIDAÇÃO DE MÉTODO PARA DETERMINAÇÃO SIMULTÂNEA DE SULFAMETAZINA, TRIMETOPRIMA E DOXICICLINA EM FORMULAÇÃO VETERINÁRIA UTILIZANDO CROMATOGRAFIA LÍQUIDA DE ALTA EFICIÊNCIA - PATRÍCIA ESPINOSA DOS SANTOS (2023)
Sulfamethazine (SMZ), trimethoprim (TMP) and doxycycline (DOXY), is a combination of drugs used in the treatment of intestinal and respiratory infections that affect poultry and pigs. The aim of this study was develop and validate a simple, sensitive and fast method for the simultaneous determination of SMZ, TMP and DOXY a veterinary formulation by high performance liquid chromatography according to the guidelines of the Validation and analytical quality control guide: pharmaceuticals in food products and veterinary medicines, RDC 166/2017 and international guides: International Conference on Harmonization (ICH) and International Association of Official Analytical Chemists (AOAC). The separation was performed on a Macherey-Nagel (MN) C8 analytical column (4 mm x 125 mm, 5 µm), with a flow rate of 0.5 mL min-1 and detection at 268 nm, 270 nm and 350 nm, for SMZ, TMP and DOXY, respectively. All measurements were performed in acetonitrile:water (45:55 v/v; pH 3.0 adjusted with phosphoric acid). The analytical curves were linear (r> 0.9997) in the concentration range of 5.0 to 35.0 μg mL−1 for SMZ, 1.0 to 7.0 μg mL−1 for TMP and 7.0 to 13.0 μg mL−1 for DOXY. The method proved to be accurate, with coefficients of variation below the maximum limit of 2.0%, robust, without significant influence of the variations used in the analysis, exact (recovery> 99%) and selective, in the assessment of interference from adjuvants. The forced degradation study was carried out under alkaline, acidic, neutral and oxidative hydrolytic conditions, and photolytic conditions, seven degradation products were identified. In accelerated stability, the sample was analyzed for 6 months (40 ± 2ºC), at the end of the study, no major variations were observed in organoleptic analysis and pH. The thermo analyses verified drug-drug compatibility, it was possible to obtain partial information on the thermal stability of SMZ, TMP and DOXY drugs in combination with binary and ternary mixtures and in the commercial sample. Thermoanalytical curves showed a reduction in the thermal stability of drugs when combined in binary and ternary mixtures when compared to individual drug analysis. In addition, the commercial sample was more stable than the ternary mixture of SMZ, TMP, and DOXY. Therefore, the developed method proved to be suitable for routine quality control analyses for the simultaneous determination of SMZ, TMP and DOXY in pharmaceutical formulations.